The Association of CSF sTREM2 With Cognitive Decline and Its Dynamic Change in Parkinson's Disease: Analysis of the PPMI Cohort - Qin, Qixiong; Wan, Hengming; Wang, Danlei; Li, Jingyi; Qu, Yi; Zhao, Jingwei; Li, Jiangting; Xue, Zheng (Frontiers in Aging Neuroscience, 2022)
Background Soluble fragment of triggering receptor expressed on myeloid cells 2 (sTREM2) in cerebrospinal fluid (CSF) is a biomarker of microglial activation and increased in several neurodegenerative diseases. However, the role of sTREM2 in Parkinson's diseases (PDs) remains unclear. This study aims to investigate whether CSF sTREM2 is changed during the pathology of PD and its association with cognitive decline. Methods We recruited 219 de novo patients with PD and 100 healthy controls from Parkinson's Progression Markers Initiative (PPMI). Cross-sectional and longitudinal associations between cognition and CSF sTREM2 were evaluated using multivariable-adjusted models. To assess the changes in CSF sTREM2 during the pathology of PD, patients were classified through the A/T classification framework with addition of α-synuclein (α-syn), which we implemented based on the CSF amyloid β-peptide 1−42 (A) and phosphorylated tau (T) and α-syn (S). Results The CSF sTREM2 did not differ between healthy controls and patients with PD or between PD clinical subgroups (p > 0.05). However, higher baseline CSF sTREM2 predicted greater global cognitive decline in patients with PD (β = −0.585, p = 0.039). Moreover, after a mean follow-up of 5.51 ± 1.31 years, baseline CSF sTREM2 that elevated in the middle tertile (HR = 2.426, 95% CI: 1.023–5.754, p = 0.044) and highest tertile (HR = 2.833, 95% CI: 1.226–6.547, p = 0.015) were associated with a future high risk of cognitive decline. Additionally, CSF sTREM2 decreased in abnormal Aβ pathology (A+) and α-syn pathology (S+) but normal tau pathology, while increased in abnormal phosphorylated tau (T+) (p < 0.05). Conclusion CSF sTREM2 may be a promising predictor for the cognitive decline in PD rather than a diagnostic biomarker. The dynamic change in CSF sTREM2 in PD may help to the monitor of neuronal injury and microglial activity.